Cranial Polypropylene Implants by Fused Filament Fabrication1 . Issue 4 (2nd December 2016) - Katschnig, Matthias; Arbeiter, Florian; Haar, Bernd; van Campe, Gord; Holzer, Clemens
Abstract : This study evaluates the feasibility and suitability of polypropylene (PP) implants produced by Fused Filament Fabrication (FFF) for the substitution of damaged cranial bone material from the polymer‐engineering point of view. The establishing of imaging methods, suitable printing material preparations, best printing practice regarding PP, and a first testing approach of the mechanical implant performance are addressed. Results indicate that PP implants are accurately printable and seem to be mechanical usable for cranial bone substitution. Further investigations concerning impact behavior and medical applicability will be conducted. Abstract : This study evaluates the technical feasibility of polypropylene (PP) implants produced by Fused Filament Fabrication (FFF) for the substitution of damaged cranial bone material. The establishing of imaging methods, suitable printing material preparations, best printing practice, and a first approach of mechanical testing are addressed. The results indicate that PP implants by FFF are accurately printable and seem to be usable for cranial bone substitution..